2004
DOI: 10.4049/jimmunol.172.12.7272
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Suppresses Prolonged Akt Activation and Expression of E2F-1 and Cyclin A in Breast Cancer Cells

Abstract: Cell cycle aberrations occurring at the G1/S checkpoint often lead to uncontrolled cell proliferation and tumor growth. We recently demonstrated that IL-1β inhibits insulin-like growth factor (IGF)-I-induced cell proliferation by preventing cells from entering the S phase of the cell cycle, leading to G0/G1 arrest. Notably, IL-1β suppresses the ability of the IGF-I receptor tyrosine kinase to phosphorylate its major docking protein, insulin receptor substrate-1, in MCF-7 breast carcinoma cells. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
3
10
0
Order By: Relevance
“…IL-1␤ in particular has been shown to downregulate the expression of insulin receptor substrate-1 and to inhibit Akt phosphorylation (5,17,24,27,45,52). This present study also found a substantial decline in the magnitude of insulin-induced Akt activation in the presence of IL-1␤.…”
Section: Discussionsupporting
confidence: 77%
“…IL-1␤ in particular has been shown to downregulate the expression of insulin receptor substrate-1 and to inhibit Akt phosphorylation (5,17,24,27,45,52). This present study also found a substantial decline in the magnitude of insulin-induced Akt activation in the presence of IL-1␤.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, lymphotoxin, TNF-a, NO, and ROS can directly kill cells. TNF-a has been shown to induce the death of neurons via a direct apoptotic effect after receptor binding and by directly interfering with intracellular substrates used by growth factors such as IGF-I and the insulin receptor (Shen et al, 2004;Venters et al, 1999). Elevated cytokines activate microglia, thereby stimulating a cycle of inflammation that recruits leukocytes, causes vascular breakdown, and directly induces cell death through the release of cytotoxic substances.…”
Section: Discussionmentioning
confidence: 99%
“…I mmune reactions as well as direct proliferative and antiproliferative effects of cytokines or cytokine-related mediators participate in the natural course of cancer (1)(2)(3)(4)(5). The recently discovered cytokine IL-22, which is structurally related to IL-10 (6), was identified as a T cell-derived inducible factor produced by IL-9-activated murine T cells (7).…”
Section: Il-22-mediated Tumor Growth Reduction Correlates With Inhibimentioning
confidence: 99%
“…Consequently, IL-22 does not induce STAT3 phosphorylation in eEND2 cells. We then studied signaling pathways involved in cell cycle control, cell proliferation and tumor growth such as ERK1/2 and AKT phosphorylation (1,15,16,(35)(36)(37)(38). IL-22 significantly inhibited these signaling pathways as shown by immunoblot analysis.…”
Section: Il-22 Activates Stat3 and Inhibits Erk1/2 And Akt Phosphorylmentioning
confidence: 99%